Impact of Post-Surgical Therapies on Endoscopic and External Dacryocystorhinostomy: Systematic Review and Meta-Analysis. Issue 6 (November 2020) - Vinciguerra, Alessandro; Nonis, Alessandro; Resti, Antonio Giordano; Bussi, Mario; Trimarchi, Matteo
Background: Epiphora is a common ophthalmologic sign that is most commonly caused by distal acquired lacrimal obstruction. Recent data have demonstrated that external dacryocystorhinostomy (EXT-DCR) and endoscopic endonasal dacryocystorhinostomy (END-DCR) can be considered the treatments of choice. However, different post-surgical medical therapies are available and are currently used to improve surgical outcomes, although no direct comparison has been performed. Objective: To analyse the influence of post-surgical medical treatments on END-DCR and EXT-DCR outcomes. Methods: A structured search was conducted using the U.S. National Library of Medicine (PubMed), EMBASE, SCOPUS, and Cochrane databases with a final search performed in May 2020. The research identified papers published later than 2000 with at least 50 single clinician procedures performed in EXT-DCR and END-DCR. Articles that studied acute infections, revision cases, mixed cohort studies of acquired and congenital obstruction, and tumour were excluded. The influence of systemic antibiotic/steroids, local application of mitomycin C, nasal/ocular antibiotic, nasal/ocular steroids and nasal decongestants was analysed. Results: In total, 11, 445 papers were selected, 2, 741 of which were reviewed after screening, and 18 included after full text review (0.6% of the initial articles reviewed) which involved 3, 590 procedures. Considering the low number of publications on EXT-DCR, statistical analysis of post-surgical therapy was not feasible. In END-DCR, the analyses were performed only for nasal steroids (p = 0.58), oral antibiotics (p = 0.45) and nasal decongestant (p = 0.27), which demonstrated no meaningful influence. Given the variable association between adjunctive medical therapies, pharmacologic molecular heterogeneity and modality/concentration of application, these results should be considered critically. Additionally, no differences were seen for application of silicone stenting, whereas, no statistical analysis was performed for mitomycin C. Conclusions: Given the high success rate of EXT-DCR and END-DCR and the heterogeneity of literature data, the effective influence of post-surgical medical therapy is difficult to identify. Future large prospective randomized studies could help in detecting the optimal adjunctive therapy for these surgeries.